2021
DOI: 10.1136/bmj-2021-067849
|View full text |Cite
|
Sign up to set email alerts
|

Giving science the finger—is the second-to-fourth digit ratio (2D:4D) a biomarker of good luck? A cross sectional study

Abstract: Objectives To explore whether random chance, weak research methodology, or inappropriate reporting can lead to claims of statistically significant (yet, biologically meaningless) biomarker associations, using as a model the relation between a common surrogate of prenatal testosterone exposure, second-to-fourth digit ratio (2D:4D), and a random indicator of good luck. Design Cross sectional study. Setting Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Thus, this association may be simply due to chance. Smoliga et al (2021) study, published in the British Medical Journal, found a significant correlation between right 2D:4D in men and good luck (i.e., poker hand rank from randomly selected playing cards as a surrogate). Their finding was not meant to provide confirmatory evidence for the association between 2D:4D and good luck.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, this association may be simply due to chance. Smoliga et al (2021) study, published in the British Medical Journal, found a significant correlation between right 2D:4D in men and good luck (i.e., poker hand rank from randomly selected playing cards as a surrogate). Their finding was not meant to provide confirmatory evidence for the association between 2D:4D and good luck.…”
Section: Discussionmentioning
confidence: 98%
“…No previous study has examined this association. The association might be due to chance, according to Smoliga et al (2021) . However, the present study’s findings may be interpretable from an evolutionary psychological perspective, although we could not conceive of its interpretation.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, it was also reported that athletes with lower 2D:4D present better performance in sumo wrestling [ 13 ] and Greco–Roman wrestling [ 14 ], and that more androgenized men tend to exhibit higher preferences for practicing combat sports (i.e., wrestling, judo, boxing, and kickboxing) rather than aerobics or team sports [ 11 , 12 ]. Furthermore, it was observed that a lower 2D:4D is associated with a lower body fat percentage, greater bone mineral content, and greater bone mineral density, especially in men, which could plausibly be related to prenatal androgen exposure [ 38 ]. Thus, 2D:4D might be a biomarker of one’s fate.…”
Section: Discussionmentioning
confidence: 99%
“…2D:4D has repeatedly been shown to correlate with various behavioral measures [ 20 ], developmental conditions [ 21 , 22 ], and even various types of cancer [ 23 , 24 ]. However, the validity of 2D:4D as a marker for prenatal testosterone exposure has been questioned [ 20 , 25 , 26 ]. Nonetheless, according to a PubMed search using the keywords “2D:4D” and “digit ratio” there were more than 100 newly published studies from 2020 till today that have investigated associations between 2D:4D and various behaviors, traits, disorders, or diseases, like muscular strength and fitness [ 5 , 27 ], parental income [ 28 ], sexual preferences [ 29 ], concentration of steroids like cortisol and vitamin D [ 30 ], thyroid disease [ 31 ], and migraine in adults [ 32 ].…”
Section: Introductionmentioning
confidence: 99%